A educação na socioeducação: um olhar para as ações educativas no contexto da medida socioeducativa de internação numa unidade de privação de liberdade - Lira, Jaqueline Alves de (2017)
This dissertation submits to investigate the education int the ambit of the social education, because it treats of a study of the educational actions in the context of the social educational measure of internment in a liberty privation unit, the proposed objective was to analyse the education in the context of a interment unit of social educational attendance fundation - Funase. The social education term appears in the Teenager and Child Statute Text - ECA, related at the integral protection paradigm and social educational measures that appear bound at the teenager pedagogical needs of attendance promise and they can be applied to those were envolved in infractions. ECA stabilishes social educational measures that will be applicable to teenagers that practise infraction, described condut as a crime or a criminal contravention, what a, in reason of attributed inimputability to that age range, it has in the social educational measures a way for teenager has opportunity to build a different life project that converged to infraction. In this educational establishments, teenagers are intern to execute the privety measure of liberty that was imposed to them. That legal text does not specify in that social educational internment measure consists in, neither it characterizes that educational stablishment. On this, and articulated to carried out studies in the research line and concentration area of the PPGDH - UFPB, Public Politcs in Human Rights, the research looked for contribution in the national legislation and in the theoretical field to dialogue about educational process that stabilishes itself in this institution called educational and, mainly, in the listening and interpretation of the social education teenagers voices inserted in the internment measure of the investigated unit. From that articulation, theory with emprirical observations, registrations and interviews with teenagers and professionals of the institution, the research permitted to identify aproximations and distancing between the reality of an educational establishment of social education that the legislation and Brazilian official documents precept, following the example of the Social Educational National Attendance System - Sinase. Teenagers are subjects of rights and, in that development stage, they need integral protection and that the opportunities and facilities of social, spiritual, moral, mental and physical development be assegurated to them, in conditions of freedom and dignity, being fit for the family, State and society in general to promote the realization of these rights. SINASE stablishes that the social education measure of internment represents a space of opportunities and guarantees of rights, that secures the necessary educational processes to development of the educational partner, being necessary public politcs that secure the human, material, physical and budget structure and necessary formation to an educational institution and stablishment.